Analysis of Magnetron-Deposited Titanium Oxynitride Coatings by Scanning Electron Microscopy and Raman Scattering; Advanced Materials Research : Radiation and nuclear techniques in material science; Vol. 1084 : Physical-Technical Problems of Nuclear Science, Energy Generation, and Power Industry (PTPAI -2014) - Arysheva G. V. Galina Vladislavovna; Ivanova N. M. Nina Mikhailovna; Konishchev M. E. Maksim Evgenievich; Pustovalova A. A. Alla Aleksandrovna; Sypchenko V. S. Vladimir Sergeevich (Materials Science and Technologies, 2015)
Title screen